Improving Care for Older Adults in China: Development of Long-Term Care Policy and System. (March 2021) - Wu, Bei; Cohen, Marc A.; Cong, Zhen; Kim, Kyungmin; Peng, Changmin
This special issue covers several important topics related to long-term care (LTC) systems and policy development in China. It provides a good contextual background on the development of the LTC system in China as well as the needs and preferences of LTC from family and older adults' perspectives. In addition, this issue covers the topic of evaluation of a recently developed long-term care nursing insurance and provides an example of family caregiving for persons with dementia within the Chinese context. The authors in this special issue also provided insights into the impact of the COVID-19 pandemic on older adults' life and LTC quality, and explored potential strategies to handle the challenges during and post-pandemic.